Інноваційні технології в управлінні персоналом на сучасному підприємстві - Погорєлова, Тетяна Олексіївна (НТУ "ХПІ", 2018)
В статті розглянуті питання щодо системи управління персоналом з точки зору інновацій, особливостей інноваційного процесу та управлінських нововведень, проблем розробки та впровадження інноваційних технологій в управління персоналом сучасного підприємства. На основі аналізу світового досвіду впровадження інноваційних технологій в управління персоналом сучасного підприємства, охарактеризовано особливості дієвих технологій у сфері управління кадрами, а саме: лізингу персоналу, кадрового аудиту та коучингу.

In the article questions of management of the personnel from the point of view of innovations, features of innovative process and administrative innovations, problems of development and introduction of innova tive technologies in personnel management of the modern enterprise are considered. Based on the analysis of the world experience in the introduction of innovative technologies in the management of the personnel of a modern enterprise, features of effective technologies in the field of personnel management, namely: personnel leasing, personnel audit and coaching are described. These technologies will allow the management of the enterprise to influence the increase in the efficiency of its activities by building a personnel management system based on innovative principles and make informed management decisions on the formation, develop ment and implementation of human resources. Implementing the development and implementation of information technologies in the personnel management system, it is necessary to assess their timeliness, ability and effectiveness, to do everything necessary to ensure that staff resistance is the smallest, and innovation efficiency is the greatest.
Innovative technologies in personnel management at a modern enterprise
Keywords: інновації; система управління персоналом; інноваційний процес; ректрутинг; innovations; personnel management system